Influence Of Mid-Cycle Pg Therapy On Fertility And Plasma Profile Of Progesterone And Biochemical Constituents In Repeat Breeding Cows And Buffaloes - Nakrani, B.B.; Dhami, A.J.; Hadiya, K.K.; Patel , J.A. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted under field conditions in Amul and Panchamrut milk-shed areas of Gujarat on 30 postpartum cows and buffaloes each of average body condition score without any visible or palpable genital abnormalities. These comprised of 20 repeat breeding (10 PG treated and 10 untreated control) and 10 normal cyclic control animals in each class. The aim was to evaluate and compare the fertility response as well as plasma progesterone and biochemical profile of repeat breeders to i/m injection of PGF2α 25 mg at mid-cycle with fix timed AI (FTAI) twice 72 and 96 hrs later (Gr-I), with those of untreated repeat breeder (Gr-II) and normal cyclic (Gr-III) controls. The oestrus induction response obtained with mid-cycle PG treatment in both cows and buffaloes was 100 % within mean intervals of 53.79±2.18 and 61.16±5.21 h, respectively, from the day of PG injection. The conception rates at induced/first oestrus and overall of 3 cycles in cows were 50 and 70%, and in buffaloes 60 and 70.00 %, respectively. The corresponding first service and overall conception rates in untreated repeat breeder cows were 20 and 30 % and buffaloes 20 and 40 %, respectively, and in normal cyclic control cows 50 and 80% and in buffaloes 40 and 70%. The repeat breeding cows and buffaloes had significantly (P<0.01) higher plasma progesterone (4.73±0.37 and 4.43±0.43 ng/ml) at the time of PGF2α injection suggesting that they all had mid cycle functional CL on the ovary. This PG injection caused rapid luteolysis and drastic (P<0.01) reduction in plasma progesterone concentrations within next 72 hrs when FTAI was done. The levels further rose significantly by day 21 post-AI due to establishment of pregnancy in 50-60 per cent of treated animals. The levels of plasma protein, cholesterol, calcium and phosphorus were not influenced by treatment or reproductive status of animals, except that among cows the minerals were significantly higher in normal cyclic than repeat breeders. Thus, the results with mid-cycle PG protocol in repeat breeding cows and buffaloes were better or at par with normal cyclic controls (50-80%), as against only 20-40% in untreated repeat breeding control groups. Hence, the mid cycle PGF2α treatment protocol can be used in repeat breeding cows and buffaloes under field conditions, provided animals have a palpable CL at the time of PG treatment and are not bred during previous cycle.